REVITALISASI KABEL DAN PEMBUATAN SISTEM OTOMATISASI LAMPU PENERANGAN JALAN MENGGUNAKAN SEMI AUTOMATIC TRANSFER SWITCH (S-ATS) DI RT 08/RW 08, KELURAHAN MERJOSARI, KOTA MALANG - Satworo Adiwidodo; Mira Esculenta; Anggit Murdani; Yuniarto Agus Winoko (Publisher UPT P2M Politeknik Negeri Malang, 2019)
RT 08 / RW 08 in the Merjosari Village area, including the area that began to develop and become a reference as a rented place for students studying in Malang. With the increasing number of entrants, the security factor is very important. To improve security for residents in the RT 08 / RW 08, one of the most important is street lighting. The team from State Polytechnic of Malang were moved to make PKM about cable revitalization and the creation of street lighting automation systems using the Semi-Automatic Transfer Switch (S-ATS). The community service activities consist of the revitalization of street lighting cables that are old and do not meet safety standards and are made an automation system for daily lights on-off power and the of semi-automatic transfer switches (S-ATS) to generators if there is a power outage at the night. So if there is a blackout at night, the street lights will stay on using the power from the generator set.